The Dynamics of Security Issues in the European Region: A Case Study of the Formation of Permanent Structured Cooperation (PESCO) - Agung Permadi; Yusran Yusran; Syahrul Awal (Andalas Journal of International Studies (AJIS), 2026)
European security has transitioned from military-centric strategies to strategies based on multidimensional threats including migration, cyber-attacks, hybrid warfare, and regional conflicts. This change indicates the transformation of the EU strategy regarding the identification and addressing of security challenges, affecting European strategic autonomy and the EU-NATO partnership. A significant part of these changes is the creation of the Permanent Structured Cooperation (PESCO) in 2017, with EU member states pledging deeper military collaboration and creating joint capabilities with increased military spending. This study examines: what was the impact of the amity in Europe on the uneven collective response of the EU to the establishment of PESCO in 2017? Through the application of qualitative comparative case study methodology and Barry Buzan and Ole Wæver’s Regional Security Complex Theory, and focusing on the concept of amity, the author aims to analyze the divide and cooperation among European states. The results show that the creation of PESCO was an institutional response to the 2014 Crimean crisis and the Russian aggression, along with the strong amity of the twenty-five founding signatories, while Denmark, Malta, and the UK remained outside of the initiative for constitutional, historical, and structural reasons, respectively, including Brexit. This demonstrates the limits of amity as a driver of a binding institutional commitment. It was shown that PESCO is a sincere but uneven response to regional security challenges and that NATO is still the predominant channel of European security.